2022
DOI: 10.2147/ccid.s345372
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Biomarkers and Pathways of Systemic Lupus Erythematosus with Skin Involvement Through GC/MS-Based Metabolomics Analysis

Abstract: Purpose Skin involvement is the second most common symptom of systemic lupus erythematosus (SLE), and the prevention of skin lesion development might benefit to lessen the system inflammation burden in SLE. However, the mechanisms of skin lesion in SLE remain unclear. Patients and Methods Metabolome based on gas chromatography-mass spectrometry (GC-MS) was used for comparison of serum metabolism among 11 SLE patients with skin lesion (SL), 10 SLE patients without skin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cyperotundone has antinociceptive, anti-inflammatory, and redox properties [ 54 ]. L-Alpha-aminobutyric acid was upregulated in autoimmune diseases [ 55 ]. Given that several highly differentially expressed proteins and metabolites in participants under hypoxia preconditioning, the functions of these molecules are mainly involved in anti-inflammation and antioxidation, and therefore, it is possible that these molecules could serve as targets to inform the AMS susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Cyperotundone has antinociceptive, anti-inflammatory, and redox properties [ 54 ]. L-Alpha-aminobutyric acid was upregulated in autoimmune diseases [ 55 ]. Given that several highly differentially expressed proteins and metabolites in participants under hypoxia preconditioning, the functions of these molecules are mainly involved in anti-inflammation and antioxidation, and therefore, it is possible that these molecules could serve as targets to inform the AMS susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…A gas chromatography/mass spectrometry study of serum metabolomics has suggested that l-alpha-aminobutyric acid, dehydroascorbic acid, glycine, and l-tyrosine may be potential markers of skin lesions in SLE. 40 Another study on multisystem involvement in SLE suggested that L-isoleucine and TAG metabolites are associated with SLE skin involvement. 14 The results of this study suggest that arginine biosynthesis, sphingolipid metabolism, alanine, aspartate, glutamate metabolism, arginine and proline metabolism, and citric acid cycle are the metabolic pathways mainly altered by skin involved SLE, some of the differential metabolites differ from other studies, probably due to the choice of the detection method and individual difference.…”
Section: Discussionmentioning
confidence: 99%